Exposure to a nocturnal light pulse simultaneously and differentially affects stridulation and locomotion behaviors in crickets - Levy, Keren; Barnea, Anat; Ayali, Amir (Frontiers in Physiology, 2023)
It is crucial for living organisms to be in synchrony with their environment and to anticipate circadian and annual changes. The circadian clock is responsible for entraining organisms’ activity to the day-night rhythmicity. Artificial light at night (ALAN) was shown to obstruct the natural light cycle, leading to desynchronized behavioral patterns. Our knowledge of the mechanisms behind these adverse effects of ALAN, however, is far from complete. Here we monitored the stridulation and locomotion behavior of male field crickets (Gryllus bimaculatus), raised under light:dark conditions, before, during, and after exposure to a nocturnal 3-hour pulse of different ALAN intensities. The experimental insects were then placed under a constant light regime (of different intensities); their behavior was continuously monitored; and the period of their daily activity rhythms was calculated. The light pulse treatment induced a simultaneous negative (suppressing stridulation) and positive (inducing locomotion) effect, manifested in significant changes in the average level of the specific activity on the night of the pulse compared to the preceding and the following nights. The transition to constant light conditions led to significant changes in the period of the circadian rhythms. Both effects were light-intensity-dependent, indicating the importance of dark nights for both individual and population synchronization.